GROUNDWATER, DRINKING WATER, ARSENIC POLLUTION, NORTH DAG - T. O. Abdulmutalimova; B. A. Revich (Юг России: экология, развитие, 2014)
In this article we studied the chemical particularities of ground water of the North Daghestan, using by population as drinking water. In particular we examined the problem of arsenic pollution.